1994
DOI: 10.1109/20.312555
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of magnetic recording heads for 2-D and 3-D finite element analysis

Abstract: Modeling of magnetic recording heads using 2-D and 3-D finite element analysis was investigated for Metal-In-Gap and thin-film heads. It is confirmed that flux concentration as well as core thickness has to be carefully modeled when trying to solve in two dimensions. It is noted that nonlinear 2-D calculations of Metal-In-Gap heads are acceptable, however, 3-D analysis is strongly recommended for thin-film heads. I.INTRODUC~ONIn designing magnetic recording heads, finite-element magnetic field analysis is one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Here, we want to discuss equation (9). If the track width of a magnetic head is more than 20 times its gap length, then the field can be modelled in terms of a two-dimensional vector [10,11]. Even in narrower track thin-film heads, it has been found that B x records only in a small band at either edge of the head track [10].…”
Section: General Relationships Between the Deflection Vector And Thre...mentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we want to discuss equation (9). If the track width of a magnetic head is more than 20 times its gap length, then the field can be modelled in terms of a two-dimensional vector [10,11]. Even in narrower track thin-film heads, it has been found that B x records only in a small band at either edge of the head track [10].…”
Section: General Relationships Between the Deflection Vector And Thre...mentioning
confidence: 99%
“…Therefore, based on the relationship shown in equation ( 8), it is difficult to get a satisfactory initial B y (x, y, 0) and the corresponding procedure similar to equations ( 17) and (18) by which to get an accurate reconstruction result of B y on the head surface is also difficult. Here, attention must be paid to equation (11), which shows the relationships between D xm and B y (x, y, z). In the following part, we propose a method to separate the deflection effect of B y (x, y, z) from the mixed deflection effects of B y (x, y, z) and B z (x, y, z) (as shown by equation ( 11)) and then use this separated deflection effect of B y (x, y, z) to obtain a satisfactory initial B y (x, y, 0) on the head surface; and, furthermore, correct the initial B y (x, y, 0) along the y direction (across the head gap) to obtain an accurate reconstruction result of B y (x, y, 0) on the head surface.…”
Section: A More Effective Procedures For Correcting B Y (X Y 0) On Th...mentioning
confidence: 99%